The Courtains and the Sixth Sense: the Invisible at Theatre (Itinera, 2017)
This article proposes to examine extra-sensorial tendencies in the theatre, the (third) eye that looks towards hidden, (para)theatrical spaces and phenomena. It begins by asserting the primordial role of the wings in the contemporary popular imagination, while underlining their absence from the theoretical corpus, even that questioning the spatial and experiential limits of performance. Then, through a number of examples taken from the historical development of the French theater, the study demonstrates how attention is consistently drawn towards invisible aspects situated offstage, thereby inciting the audience to further hone a sixth sense so as to fully grasp the performance.